Profil Keterampilan Mengajar Calon Guru Fisika pada Mata Kuliah Microteaching dengan Pembelajaran Berbasis Proyek - Derlina Derlina; Wawan Bunawan; Sabani (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to analyze the improvement of teaching skills of prospective physics teachers in Unimed Physics Education Study Program. The research method used is classroom action research method with Kemmis and Mc. Taggart model by applying project-based learning model in microteaching course. The research stages consist of planning, action, observation and reflection.Â  The research subjects were 2020 batch students who took microteaching courses in the even semester of 2022/2023 year academic as many as 10 people. This research consists of 3 cycles with 2 meetings in each cycle. The instruments used in this study were questionnaires, teaching skills assessment rubrics and learning observation sheets. Data collection was carried out by giving questionnaires and direct observation of learning activities carried out by prospective teacher students. Data analysis techniques were carried out with gain test analysis. The average score of prospective teachers' teaching skills at the time of cycle 1 was 36.9 in the very unskilled category, to 81.6 in the skilled category in cycle 3, experiencing an increase in scores from cycle 1 to cycle 3 with an N-gain score = 0.7 in the moderate category.Â  Based on the results of the study, it can be concluded that project-based learning in microteaching courses can improve the teaching skills of prospective physics teachers in microteaching courses.